Safe conduct of traffic through highway construction and maintenance zones. - National Cooperative Highway Research Program; National Research Council (U.S.). Transportation Research Board (Washington, D.C. Transportation Research Board, 1978)
"A staff digest of the progress and status of NCHRP Project 20-5, "Synthesis of information related to highway problems," for which the Transportation Research Board is the agency conducting the research."
Caption title.
At head of title: National Cooperative Highway Research Program.
February 1978.
Keywords: Highway research -- United States